The Union of the Comoros : Jumpstarting Agricultural Transformation - World Bank Group (World Bank, Washington, DC, 2019)
This report is the World Bank’s first Agriculture Sector Review (ASR) for the Union of the Comoros, the first analytic product in the Bank’s reengagement with the sector after a gap of two decades. This review is a stocktaking exercise that aims to provide the Government of Comoros with the evidence base necessary for strategic policymaking and smart investments critical to jumpstarting agricultural transformation in the country. In the short-term, the findings from this ASR are intended to launch an evidence-based, participatory, and inclusive consultation process that feeds into an updated sector strategy and investment plan that charts the path towards agricultural transformation.